Scientometrics Approach to Research in Ovine Mastitis from 1970 to 2019 (with a Complete List of Relevant Literature References) - Daphne T. Lianou; George C. Fthenakis (Pathogens, 2020)
The present study is a scientometrics evaluation of refereed publications on bacterial mastitis in sheep; the objectives were the evaluation of the relevant papers and the presentation of quantitative characteristics regarding their scientific content and bibliometric details. The Web of Science platform was used with search terms: [mastitis OR *mammary infection*] AND [sheep OR ewe* OR ovine] for papers from 1970 tο 2019; only ‘articles’, ‘reviews’, ‘proceedings papers’, or ‘data papers’ were evaluated, whilst documents related solely to contagious agalactia, mammary aspects of lentiviral infections, or infections of the teats and the udder skin were excluded. Finally, 580 papers were considered in detail. The number of published papers increased from 8 during the 1970s to 273 during the 2010s. These papers originated from 43 countries (most from Greece or Spain, n = 87 from each) and 240 institutions (145 universities and 95 other establishments), of which 35 produced ≥ 5 papers each. Most papers present original studies (n = 539) with a few reviews (n = 41). The original papers refer to dairy (n = 428), meat (n = 113), or wool (n = 1) production systems and present field (n = 329), laboratory (n = 163), or experimental (n = 67) work; the papers report aetiology (n = 146), risk factors (n = 100), pathogenesis (n = 92), diagnosis (n = 88), effects (n = 66), treatment (n = 50), control (n = 36), or descriptive epidemiology (n = 32) of the disease. Papers related to dairy production present more field and fewer experimental work than papers related to meat production; also, in papers describing work performed in dairy sheep, studies about aetiology, risk factors, and diagnosis of the disease predominate, whilst in papers performed in meat sheep, studies about aetiology, pathogenesis, and effects/diagnosis are reported more often. The papers were published in 175 scientific journals (most in Small Ruminant Research, n = 90, or Journal of Dairy Science, n = 54). On average, the papers received 16.8 total citations and 1.6 yearly citations (h-index = 47). Most papers were published in Scimago classification Q1 (n = 240) or Q2 (n = 230) journals and received 23.4 or 15.4 total citations, respectively. Reviews received more citations than original papers; among the latter, papers with work referring to dairy production received more yearly citations than papers referring to meat production; no differences in citations were seen according to type of work or mastitis aspect covered. Most citations were received by papers from France. Papers published in Journal of Dairy Science or Small Ruminant Research received the most citations. In total, there were 1558 individual authors of the papers, with 24 authors having co-authored > 10 papers each (max: 73 papers); on average, there were 5.2 co-authors per paper (min–max: 1–25). Average number of co-authors progressively increased from 2.1 in the 1970s to 6.3 in the 2010s, with original papers having a higher number of co-authors than reviews: 5.3 and 3.7, respectively. Papers from France had highers number of co-authors (7.9). The findings of this first ever scientometrics study into ovine mastitis indicate that the disease has not been studied as other sheep diseases and that future studies in it should be directed to its control.